2016
DOI: 10.1371/journal.pone.0154192
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Dexmedetomidine as a Sedative Premedication for Patients Undergoing Suspension Laryngoscopy: A Randomized Double-Blind Study

Abstract: BackgroundIntranasal dexmedetomidine, a well-tolerated and convenient treatment option, has been shown to induce a favorable perioperative anxiolysis in children. We investigate intranasal dexmedetomidine as a sedative premedication for anesthesia recovery in an adult population.MethodsA prospective randomized controlled trial; 81 adult patients scheduled for elective suspension laryngoscopy received intranasal dexmedetomidine (1 μg∙kg–1) or a placebo 45–60 min before anesthetic induction. Extubation time was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 36 publications
1
14
0
1
Order By: Relevance
“…Postoperative agitation in children undergoing different surgical procedures has been widely investigated. However, studies on postoperative agitation in children undergoing dental treatment under general anesthesia are few [5][6][7]. In this study, the effects of intranasal dexmedetomidine and oral midazolam were compared with those of preoperative sedation and postoperative agitation in 3-6-year-old children under dental treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative agitation in children undergoing different surgical procedures has been widely investigated. However, studies on postoperative agitation in children undergoing dental treatment under general anesthesia are few [5][6][7]. In this study, the effects of intranasal dexmedetomidine and oral midazolam were compared with those of preoperative sedation and postoperative agitation in 3-6-year-old children under dental treatment.…”
Section: Introductionmentioning
confidence: 99%
“… 24 Furthermore, it has been demonstrated that Dex can reduce the hyperalgesia caused by remifentanil and pain stimulation, and can yield global haemodynamic stability and prevent violent injury to the throat and vocal cord. 25–27 Notably, previous reports have confirmed the efficacy of intranasal Dex as a sedative premedication to induce a favourable perioperative anxiolysis 28 and reduce emergence agitation during recovery from general anesthesia. 29 In addition, Rani et al 30 found that a single dose of Dex, administered intravenously 15 min prior to extubation, could suppress the airway reflex during recovery from general anaesthesia.…”
Section: Discussionmentioning
confidence: 89%
“…In this regard, the potential role of intranasal dexmedetomidine for FD patients is appealing. Intranasal dexmedetomidine has been used to pre-medicate pediatric patients undergoing diagnostic and therapeutic procedures to provide light sedation and blunt sympathetic activity [2, 8, 15, 18, 28]. Because initial management of FD crises typically occurs at home, the availability of a medication with rapid onset, effectiveness via the intranasal route, and minimal risk of respiratory depression, would pose a significant therapeutic innovation.…”
Section: Discussionmentioning
confidence: 99%